PENDUGAAN KEKAKUAN KAYU BORNEO DENGAN METODE GELOMBANG ULTRASONIK - . Syahidah; Tekat Dwi Cahyono (PERENNIAL, 2010)
Borneo wood is a name for various species commercial wood. The aimed of this study are measured stifness (MOE) of borneo wood using non destructive method i.e. ultrasonic wave. Fiveteen beam sample were produced from borneo wood about 8 cm thick and 12 cm width with 400 cm, 250 cm and 150 cm length. Beam with 250 cm and 150 cm length produced from beam with 400 cm length after stifness test have done using ultrasonic (dynamic test) and UTM (static test). Result showed that dynamic MOE of borneo wood for 400 cm, 250 cm and 150 cm length, are 19.10 G.Pa, 18.48 G.Pa and 15.90 G.Pa, respectively. Wood about 400 cm and 150 cm length were different significantly. Result also showed that dynamic MOE of borneo wood 30% higher than static MOE at vertical position test for beam with 400 cm length and 20% higher for horisontal position at the same testing method. Key words : Borneo wood, stifness, ultrasonic, MOE, MOR